THE ARTICLE DISCUSSES ENHANCING TEACHING IN AN ENRICHED LEARNING ENVIRONMENT FOR ENGLISH LANGUAGE SCHOOL STUDENTS - Qazoqova Dilnoza Qobil kizi; Norbotayev Khoshbok Bobonazarovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
It touches upon a range of modern teaching technologies that aid in improving the quality of biology education, boosting motivation, shaping students' functional literacy and core competencies, and fostering the development of students' potential abilities.